The Utilization of Social Media as Marketing Communications Medium on Pandemic Situation (Study on Bogor Botanical Garden) - Safitri, Rika Nurismah; Pitoyo (International Journal of Educational Research & Social Sciences, 2022)
The tourism industry is one of the sectors that impacted by the covid-19 pandemic. The Bogor Botanical Garden is the most visited tourist spot in Bogor City in 2016. But since December 2019 the coronavirus has spread around the world, until WHO declared it a global pandemic. Therefore, people are required to stay at home to reduce interaction with other individuals and reduce the spread of the corona virus. Many tourist attractions can not survive until they have to close. However, Bogor Botanical Garden still survives during this pandemic. Because of these problems, researchers aim to examine marketing communications conducted by Bogor Botanical Garden by utilizing social media. The research used qualitative method by taking data in an interview. The theories used are the Computer Mediated Communication Theory or CMC and constructivism paradigm. The results showed that The Botanical Garden has several social media whose main purpose is to conduct marketing communication to its consumers. The Botanical Garden also implements some form of CMC. The social media used by the Botanical Gardens are website, Facebook, Instagram, twitter, YouTube, and ticktock. There are four forms of CMC found in the Bogor Botanical Gardens, namely social media, instant messages, video conferences, and email.